2023
DOI: 10.1002/ece3.10232
|View full text |Cite
|
Sign up to set email alerts
|

Which demographic processes control competitive equilibria? Bayesian calibration of a size‐structured forest population model

Abstract: In forest communities, light competition is a key process for community assembly. Species' differences in seedling and sapling tolerance to shade cast by overstory trees is thought to determine species composition at late-successional stages. Most forests are distant from these late-successional equilibria, impeding a formal evaluation of their potential species composition. To extrapolate competitive equilibria from shortterm data, we therefore introduce the JAB model, a parsimonious dynamic model with intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(21 citation statements)
references
References 76 publications
1
20
0
Order By: Relevance
“…Our simulations largely support the prediction that Fagus predominates in mesic environmental conditions while other species become more prevalent at the extremes of soil pH and water gradients (Section 4.1). Moreover, we substantiate the theory with demographic analysis (Section 4.2): In a previous study, Heiland et al (2023) showed that di erences in mean demographic rates between Fagus and others, especially the shadetolerance of its saplings, explain Fagus' predominance in its core range (these results are largely consistent with the estimates presented in Table 2). Expanding on this approach, here we introduce a model with environmentally-responsive demographic rates to explain the environmental variation of Fagus' relative abundance and why other species prevail towards more stressful environmental conditions.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Our simulations largely support the prediction that Fagus predominates in mesic environmental conditions while other species become more prevalent at the extremes of soil pH and water gradients (Section 4.1). Moreover, we substantiate the theory with demographic analysis (Section 4.2): In a previous study, Heiland et al (2023) showed that di erences in mean demographic rates between Fagus and others, especially the shadetolerance of its saplings, explain Fagus' predominance in its core range (these results are largely consistent with the estimates presented in Table 2). Expanding on this approach, here we introduce a model with environmentally-responsive demographic rates to explain the environmental variation of Fagus' relative abundance and why other species prevail towards more stressful environmental conditions.…”
Section: Discussionsupporting
confidence: 88%
“…The JAB model (Heiland et al, 2023) is a simple dynamic forest population model that includes three size stages including the sapling stage. The model concentrates on competition between multiple species and on the species-specific sapling dynamics by assuming a simple two-layer size structure (see also Valladares & Niinemets, 2008; Cordonnier et al, 2019)…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations